Bidirectional relationship between health behavior and subjective well-being in adults - Stenlund, Säde (fi=Turun yliopisto|en=University of Turku|, 2022)
Unhealthy behavior increases the unsustainable burden of chronic diseases on health care and changing health behavior is often personally challenging. The present thesis provides a new, positive perspective to investigating health behavior changes by exploring their association with subjective well-being. So far, their mutual associations have been studied in cross-sectional settings. Longitudinal studies are sparse, usually unidirectional, have focused on only one health behavior, and have commonly been based on follow-up times of only a few years. The aim of the present thesis is to explore this bidirectional relationship and to determine whether health behavior better predicts subsequent subjective well-being than vice versa in a longitudinal setting. The HeSSup (Health and Social Support) study represented a population-based random sample (n = 11,927) of the Finnish working-age population. The longitudinal and reciprocal relationships between health behavior and subjective well-being among the participants were explored using linear regression and structural equation modeling in a nine-year follow-up (2003–2012). The sum score of self-reported dichotomized health behaviors included physical activity during leisure time and commuting, dietary habits based on ten food items, alcohol consumption below the risk use level, and smoking status. The four-item life satisfaction scale including three life assessments (i.e., happiness, interestingness, and easiness) and perceived loneliness was used as an indicator of subjective well-being. In the nine-year follow-up based on observational results, a higher number of beneficial health behaviors and positive changes in these behaviors predicted improved subjective well-being in both linear regression and structural equation modeling. Subjective well-being and positive changes in this well-being predicted subsequent health behavior in linear regression modeling and potentially through an alternative pathway, but not directly, in structural equation modeling. Health behavior appears to be a stronger predictor of subjective well-being than vice versa. Improved subjective well-being could serve as a motivator for health behavior change, and on the other hand, targeting subjective well-being could support a positive health behavior change, especially on an everyday level. In conclusion, including subjective well-being perspectives in health care and policies could help support health behavior changes.

Elintapojen ja subjektiivisen hyvinvoinnin kahdensuuntainen yhteys aikuisilla Huonot elintavat kasvattavat kroonisten sairauksien kestämätöntä terveydenhuollon taakkaa, ja elintapamuutokset ovat usein yksilölle haastavia. Tämä väitöskirja elintapojen ja subjektiivisen hyvinvoinnin yhteydestä tarjoaa uuden ja positiivisen näkökulman elintapamuutosten tukemiseen. Yhteys on todennettu poikkileikkaustutkimuksissa, mutta seurantatutkimuksia on vähän, ja niissä on monia rajoituksia. Seuranta- ajat ovat useimmiten lyhyitä ja tarkastelu yhdensuuntainen keskittyen yhteen elintapaan. Väitöskirjan tavoite on syventää ymmärrystä tästä kahdensuuntaisesta yhteydestä ja tarkastella ennustavatko elintavat subjektiivista hyvinvointia vahvemmin kuin päinvastoin yhdeksän vuoden seurannassa. HeSSup-tutkimus (Health and Social Support, terveys ja sosiaalinen tuki) perustuu satunnaiseen väestönotantaan työikäisistä suomalaisista (n = 11,927). Heidän elintapojen ja subjektiivisen hyvinvoinnin keskinäisiä vaikutuksia tarkastellaan pitkittäisasetelmassa (2003–2012) sekä lineaarisin mallein että rakenneyhtälömallinnuksella. Itseraportoitujen kaksiluokkaisten elintapojen summamuuttuja kattaa neljä keskeisintä kroonisiin sairauksiin vaikuttavaa elintapaa: vapaa-ajan ja työmatkojen liikunnan, ruokavalion kymmenen ruoka-ainekategorian perusteella, kohtuullisen alkoholin käytön ja tupakoimattomuuden. Neljän muuttujan elämään tyytyväisyyden mittari sisältää kolme elämän arviota elämän onnellisuudesta, kiinnostavuudesta ja helppoudesta sekä koetun yksinäisyyden. Mittaria käytetään kuvaamaan subjektiivista hyvinvointia. Yhdeksän vuoden seurannassa useampi suotuisa elintapa ja niiden positiiviset muutokset ennustivat subjektiivista hyvinvointia niin lineaarisissa kuin rakenneyhtälömalleissa havainnoivassa tutkimusasetelmassa. Sen sijaan subjektiivinen hyvinvointi ja sen positiiviset muutokset ennustivat parempia elintapoja lineaarisissa malleissa sekä vaihtoehtoista reittiä mutta eivät suoraan rakenneyhtälömallinnuksessa. Elintavat vaikuttivat ennustavan subjektiivista hyvinvointia vahvemmin kuin subjektiivinen hyvinvointi ennusti elintapoja. Elintapojen positiiviset vaikutukset subjektiiviseen hyvinvointiin voisivat motivoida elintapamuutoksiin. Subjektiiviseen hyvinvointiin vaikuttaminen voisi myös tukea elintapamuutosten onnistumista päivittäistasolla. Subjektiivisen hyvinvoinnin huomioiminen terveydenhuollossa sekä poliittisessa päätöksenteossa voisi auttaa elintapamuutosten tukemisessa